Taxonomic notes on Thrixspermum (Orchidaceae: Aeridinae), with five new species from Thailand - Toolmal, Nopparut; Suddee, Somran; Culham, Alastair; Utteridge, Timothy M. A.; Schuiteman, André (Phytotaxa, 2023)
Five new species of Thrixspermum (Orchidaceae) are described from Thailand, two from sect. Dendrocolla: T. alboluteum (South-West floristic region), T. praetermissum (East); and three from sect. Thrixspermum: T. simile (South-East), T. flammeum (East), T. polystictum (East). Descriptions, illustrations, notes on distribution, ecology, phenology, conservation status, and morphological comparisons with allied species are provided. Thrixspermum musciflorum and its variety nilagiricum are reduced to the synonymy of T. formosanum. Thrixspermum album is reduced to the synonymy of T. pulchellum. We select a lectotype and an epitype for T. trichoglottis (Hook.f.) Kuntze and provide a detailed description of this common but so far incompletely known species.